1990
DOI: 10.1002/ep.670090320
|View full text |Cite
|
Sign up to set email alerts
|

Removal of organics from offshore produced waters using nanofiltration membrane technology

Abstract: The separation of oil and produced water mixtures from oil and gas producing w e b has traditionaUy been accomplished by gravity settlers (e.g., multi-phase separators, skimmers, andflotation ceh). However, current EPA regulations on the organic content of discharged produced water have reached the limits of these separation techniques. The industry is in need of new technologies to treat these waters. One such technology that we have found promising is organicslwater separation by nano$ltration membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2025
2025

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…A key parameter is feedwater pH, which determines the surface charge on membranes and the speciation of target compounds, and thereby influences the electrostatic repulsion of charged solutes (e.g., Hagmeyer and Gimbel 1998). A similar relationship between pH and rejection of organic solutes by nanofiltration membranes has been demonstrated for carboxylic acids, benzoic and sulphonic acids (Dyke and Bartels 1990;Bellona and Drewes 2005). For example, low solution pH decreases the rejection of natural organic matter by condensing its molecular structure (Braghetta et al 1997).…”
Section: Nanofiltrationmentioning
confidence: 88%
See 1 more Smart Citation
“…A key parameter is feedwater pH, which determines the surface charge on membranes and the speciation of target compounds, and thereby influences the electrostatic repulsion of charged solutes (e.g., Hagmeyer and Gimbel 1998). A similar relationship between pH and rejection of organic solutes by nanofiltration membranes has been demonstrated for carboxylic acids, benzoic and sulphonic acids (Dyke and Bartels 1990;Bellona and Drewes 2005). For example, low solution pH decreases the rejection of natural organic matter by condensing its molecular structure (Braghetta et al 1997).…”
Section: Nanofiltrationmentioning
confidence: 88%
“…As previously discussed, Peng et al (2004) demonstrated successful removal of naphthenic acids and divalent salts from oil sands process waters with several types of nanofiltration membranes. In another study, pilot-scale (14 m 3 /d) nanofiltration of offshore produced water achieved 72%-89% rejection of freon-extractable organics and 15%-20% rejection of salts (Dyke and Bartels 1990).…”
Section: Nanofiltrationmentioning
confidence: 96%
“…In order to effectively reduce or eliminate toxicity of OSPW, a treatment approach that can directly target NAs is required. Several researchers explored the effectiveness of using different technologies in the treatment of OSPW, such as: adsorption (Hansen and Davies, 1994;Marr et al, 1996;Adhoum and Monser, 2004), micro-and ultrafiltration (Bilstad and Espedal, 1996;Lin and Lan, 1998;Campos et al, 2002), nanofiltration, reverse osmosis, and electrodialysis (Dyke and Bartels, 1990;Agenson et al, 2003;Peng et al, 2004), biological treatment (Doran et al, 1998;Tellez et al, 2002;Campos et al, 2002), and advanced oxidation (Bettle and Tittlebaum, 1995;Li et al, 2006;Scott et al, 2008;Martin et al, 2010;He et al, 2012He et al, , 2010Garcia-Garcia et al, 2011;Gamal El-Din et al, 2011;Pérez-Estrada et al, 2011;Anderson et al, 2012;Pereira et al, 2013;Hwang et al, 2013). Allen (2008b) had reviewed the above emerging technologies in the treatment of the OSPW.…”
Section: Treatment Of Naphthenic Acidsmentioning
confidence: 99%
“…Meanwhile, these waters are mostly at high temperature and pH, which can affect the membrane integrity of current commercial membranes. In some applications, these streams must be cooled or pH tuned solely to accommodate a membrane separation process, after which the processed fluid will be readjusted back to an initial condition (e.g., pH) to optimize steam production reliability [26][27][28]. This temperature and pH adjustment requires a significant amount of energy and chemicals.…”
Section: Oil Sands-produced Water Treatment By Nanofiltrationmentioning
confidence: 99%